(untitled) (Western European Journal of Medicine and Medical Science, 2026)
In recent years, the problem of the impact of adverse environmental factors on reproductive health has become increasingly relevant. One of the most common toxic agents is carbon monoxide (CO), which is formed during incomplete combustion of carbon-containing substances and is widely found in urban areas, industrial production and domestic sources. These findings suggest that prolonged exposure to carbon monoxide leads to significant alterations in uterine microcirculation and tissue organization, which may adversely affect reproductive function